THE STUDY OF THE CHARACTERISICS AND VOLUME OF GARBAGE IN THE OFFICE OF KUPANG HEALTH POLYTECNIC IN 2013 - AGUSTINA AGUSTINA; RAMBU A.P. NDAWA REHA (JURNAL INFO KESEHATAN, 2014)
Garbage is a growing media of bacteria or parasites and vectors of some diseases sush as flies, cockroasches, mosquitos and rats. The purpose of this studywas to determine the characteristics and waste volume in all departemen of Kupang Health Polyechnic.The type of the study was descriptive research which has explained about the characteristics and volume of garbage in office. Observed variables were the characteristics and volume of garbage in all Kupang Health Polytecnic offies. The date were primary data collected by on field measurements and then descriptively analyzed.The result of the study showed that all waste in all department of Kupang Health Polytecnic offices have Rubbish characterized and the average volume of garbage in Enviromental Health Departemen was 39 litters/day , Nutrition Departemen was 42 litters/day, the Analysis of Health department was 53 litters/day, And Directorate of Poltekkes office 54 litters/day.From the above result can be concluded that all garbage had rubbish characteriszed and different averages of waste volumeon each office per-day. It is suggested to all of the offices of Kupang Health Polytecnic to provide the bin based on type of garbage and also garbage paper can be reused in another function.